2006
DOI: 10.1002/anie.200602854
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structure Assignment of (+)‐Hexacyclinol

Abstract: Structure assigned: The revised structure of (+)‐hexacyclinol (1) proposed recently was confirmed following the total synthesis of the natural product. The synthesis was designed around the highly stereoselective Diels–Alder dimerization of an epoxyquinol monomer, followed by intramolecular acid‐catalyzed cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 20 publications
2
48
1
Order By: Relevance
“…[61] An analysis of the original report [62] suggests that at least three errors were made: H (12) is located at δ = 3.62 ppm, not 3.55 pm; H (12) is directly attached to a carbon atom at δ = 41.0 ppm, not 40.4 ppm; and H(19) is directly attached to a carbon atom at δ = 40.6 ppm, not 40.9 ppm. These errors likely resulted from insufficient carbon resolution in the original heteronuclear correlation spectra.…”
Section: Verifying Proposed Structuresmentioning
confidence: 97%
“…[61] An analysis of the original report [62] suggests that at least three errors were made: H (12) is located at δ = 3.62 ppm, not 3.55 pm; H (12) is directly attached to a carbon atom at δ = 41.0 ppm, not 40.4 ppm; and H(19) is directly attached to a carbon atom at δ = 40.6 ppm, not 40.9 ppm. These errors likely resulted from insufficient carbon resolution in the original heteronuclear correlation spectra.…”
Section: Verifying Proposed Structuresmentioning
confidence: 97%
“…One of the most recent and striking examples of the successful application of the QM approach was described by Rychnovsky [26] who refuted the incorrect structure of hexacyclinol proposed by Grafe et al [27] and suggested another structure which was then unambiguously proved by synthesis and X-ray analysis. [28] A systematic method to confirm the structure of hexacyclinol using Structure Elucidator was also described elsewhere. [29] QM chemical shift prediction is rather time consuming relative to other approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The intriguing story about the structure elucidation of hexacyclinol was described in a series of publications. [61][62][63][64][65] 13 C chemical shift calculation should be considered as the most severe filter to reject all invalid structures and to select the most probable one. However, the average deviations between experimental and predicted spectra that serve as effective criteria for structure assessment are calculable only if chemical shift assignment is completed.…”
Section: Discussionmentioning
confidence: 99%